Pertumbuhan Anak Kambing Peranakan Etawah (PE) Sampai Umur 6 Bulan di Pedesaan - Sulaksana, Indra (Fakultas Peternakan Universitas Jambi, 2008)
The research on the growth of Peranakan Etawah goat until six months-old during rainy and drought season was done in Petaling Jaya village Kecamatan Kumpeh Kabupaten Muaro Jambi. Ninety three Peranakan Etawah goats were used as sample based on the date of birth. Survey method was used to obtained satisfactory data, throughout interview, recording and weighting of body goat. Body weight, weaning weight, 6 months old-weight, pre weaning weight gain and 6 months old-weight gain were recorded during observation. Result showed that average of birth weight; weaning weight; 6 months old-weight; pre weaning weight gain and body weight gain obtained were 2.33 ± 0.45 kg; 9.72 ± 194 kg; 13.24 ± 3.28 kg; 81.76 ± 20.69 and 46.07 ± 24.92 gr, respectively. In conclusion, the growth of Peranakan Etawah goat was not affected (P>0.05) by season for weaning weight, 6 months old-weight and pre weaning weight gain as well, but season had significantly effect (P<0.05) on weight of birth and 6 months old weight gain.